Development of Interdisciplinary-Based Islamic Religious Education Teaching Materials in State Universities - Muhammad Arifin; Sumiah Nasution; Sanudin Ranam; Siti Fuadah; Muhammad Aunurrochim (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This research aims to develop interdisciplinary Islamic Religious Education (PAI) teaching materials tailored to the needs of students at public universities (PTU). The interdisciplinary approach is used in response to the dichotomy between religious studies and general studies that is still prevalent in the higher education system. By integrating Islamic values into various disciplines such as science, technology, economics, and social studies, PAI teaching materials can provide students with a more contextual and applicable understanding. The research method used is Research and Development (R&D) with qualitative and quantitative approaches, involving needs analysis, teaching materials design, expert validation, and limited student trials. The results indicate that interdisciplinary PAI teaching materials can increase student engagement, strengthen the relevance of PAI in the context of modern science, and shape critical and adaptive religious character. These findings suggest that integrating Islamic values into PAI teaching materials can be an effective strategy in building higher education that is not only intellectually superior, but also morally and personally developed. This study recommends that public universities adopt a broader interdisciplinary approach in developing Islamic Religious Education (PAI) curricula to comprehensively address the challenges of Society 5.0.